Creating citizen-consumers: changing relationships and identifications, 2003-2005 - Clarke, John (UK Data Service, 2007)
This project was situated in a number of significant political, policy and academic debates. Citizens and consumers are typically thought of as antagonistic terms, reflecting the institutional oppositions between state and market, public and private, collectivism and individualism. As a result, addressing citizens as consumers of public services implies a shift from the collectivist and state-centric formations of post-war welfarism to the individualist and market-centric formations associated with neo-liberalism. Although it derives from the Conservative governments of the 1980s and 1990s, Labour governments since 1997 have placed the citizen-consumer in a central role in the modernisation and reform of public services in the UK. A model of consumer choice has increasingly been identified as the means of empowering the citizen-consumer. The project centred on two key propositions. Firstly, policies on consumerism and choice are likely to produce shifting relationships between the providers and users of public services, but these may be service-specific. Secondly, the figure of the citizen-consumer may not capture the complexity of service user identifications. Also, the project had four main objectives: to trace the development of consumerist relationships in British social policy; to explore the forms such relationships take in different services, sectors and political cultures; to examine how consumer identities articulate with other identities among service users and service providers; and to situate the shift to consumerist relationships in social policy in the UK in an international context.